Rhabdomyoblastic Differentiation in Metastatic Melanoma: Making Sense of a Rare but Complex Form of Mimicry. (September 2014) - Reilly, Daniel J.; Volchek, Mila; Ting, Jeannette W. C.; Allan, Prue; Findlay, Michael W.
A case of melanoma with rhabdomyoblastic differentiation is presented in the context of the previously reported cases. The emerging literature seeking to identify the molecular basis of rhabdoid and rhabdomyoblastic differentiation, as well as their poor prognosis, is reviewed. The combination of a diverse range of morphology and the potential for spontaneous primary tumor regression, despite metastasis, makes the accurate diagnosis of melanoma challenging. Histopathology review is often recommended in these cases, as is referral to a specialized cancer center for discussion in a multidisciplinary meeting. Improved recognition of this rare pattern of melanoma morphology may provide the means for omics-based techniques to identify novel therapeutic targets to improve the prognostic outlook for these patients.